If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying bx + -6y = -17 Solving bx + -6y = -17 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '6y' to each side of the equation. bx + -6y + 6y = -17 + 6y Combine like terms: -6y + 6y = 0 bx + 0 = -17 + 6y bx = -17 + 6y Divide each side by 'x'. b = -17x-1 + 6x-1y Simplifying b = -17x-1 + 6x-1y
| x=(x-1*0.94)+77000 | | 4=5+n | | -6=x-17 | | 61-4=23x+16 | | 4(n+7)=n-(4-n) | | 3x+10=23-8x | | -17.5=3.5c | | 4(n+7)= | | y=2x^3+x^2-x | | 4(x-72)=-16 | | 3(x-5)+4(2x+3)=30 | | 6n+(7n)=42 | | 9x=12-3y | | 7n+3=2n+33 | | 3-5(2x-7)=5-(4-2x) | | 7(x+4)+5x=30 | | n+(-2)=-14 | | 4(Y-3)-6(y+1)=4(3y+4)-2(8-6y) | | r+(-3)=10 | | -12+10y=15y+3 | | 390=30*3+42h+195 | | x-(-6)=20 | | x-.1x=27.76 | | 9n+8=71 | | 96-28*x=-x^2 | | -3y+2= | | 5n-15=15 | | 96-28x=x^2 | | ln(x+1)=ln(3x+3) | | -2(4-3*0.7)= | | 4x^3+3x^2-2=0 | | p-0.1=1.4 |